Polityka Austrii wobec imigracji i unijnej polityki imigracyjnej (Politeja, 2024)
AUSTRIA’S POLICY TOWARDS IMMIGRATION AND EU IMMIGRATION POLICYAustria’s migration policy has changed over the past years. The analysis of contemporary immigration processes taking place in Austria is not only an interesting, but also a very dynamic issue. The mentioned changes had an influence on internal situation of the country, as well as on the attitude towards the EU migration policy. The aim of the analysis will be to diagnose the main line of Austrian policy towards contemporary migration processes. The research goal was to indicate the nature of changes in Austria’s policy towards immigration and their causes. The analysis concerned both the internal dimension and Austria’s activity on the European forum. The thesis was accepted that these two levels are interconnected, and Austria’s attitude towards the EU immigration policy is a reflection of the changes that can be observed in the state’s internal policy. The article first presents the stages of shaping Austria’s internal immigration policy, and then the state’s attitude towards the EU proposals to solve the so-called migration issue. With regard to the second issue, the focus was on two elements: the European Union’s response to the events related to the outbreak of the migration crisis and the work on a new pact on migration and asylum, undertaken in connection with the abandonment of the forced relocation program.